2001
DOI: 10.1029/2001gl013587
|View full text |Cite
|
Sign up to set email alerts
|

Coherent intraseasonal oscillations of ocean and atmosphere during the Asian Summer Monsoon

Abstract: Abstract.The space-time evolution of the ocean and atmosphere associated with 1998-2000 monsoon intraseasonal oscillations (ISO) in the Indian Ocean and west Pacific is studied using validated sea surface temperature (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
149
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(166 citation statements)
references
References 21 publications
17
149
0
Order By: Relevance
“…The observed SST-precipitation quadrature phase relationship on intraseasonal timescales (Shinoda et al 1998;Senguta et al 2001) has suggested that interactive air-sea coupling represents an important process for MJO dynamics (Wang and Xie 1998). On the one hand, the (Senguta et al 2001;Waliser et al 2003), oceanic mixed-layer entrainment (Fu et al 2003;Saji et al 2006), and horizontal advection (Han et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed SST-precipitation quadrature phase relationship on intraseasonal timescales (Shinoda et al 1998;Senguta et al 2001) has suggested that interactive air-sea coupling represents an important process for MJO dynamics (Wang and Xie 1998). On the one hand, the (Senguta et al 2001;Waliser et al 2003), oceanic mixed-layer entrainment (Fu et al 2003;Saji et al 2006), and horizontal advection (Han et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the (Senguta et al 2001;Waliser et al 2003), oceanic mixed-layer entrainment (Fu et al 2003;Saji et al 2006), and horizontal advection (Han et al 2007). On the other hand, the resultant intraseasonal SST anomaly feeds back to organize MJO convection and associated circulations through enhancing boundary-layer convergence (Wang and Xie 1998;Waliser et al 1999) and surface evaporation (Fu et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These anomalies, in turn, generate further SST change through diabatic heating across the sea surface and generation of oceanic waves. A possibility of such air-sea interactions in the warm pool region has been reported for phenomena at intraseasonal timescale [Zhang and McPhaden, 2000;Shinoda and Hendon, 2001;Sengupta et al, 2001b;Saji et al, 2006;Han et al, 2007] and for interannual variations, such as the Indian Ocean dipole mode event [Saji et al, 1999;Webster et al, 1999;Murtugudde et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…As responses to such significant ISV in the atmosphere, upper-ocean variability is also expected to have large variability at the intraseasonal time-scale. For example, Sengupta et al [2001b], Saji et al [2006], and Han et al [2007] demonstrate the possibility of the air-sea interaction in the eastern Indian Ocean at the intraseasonal timescale by analyzing observed and simulated data. Recent studies also reveal that multiscale air-sea interactions between intraseasonal and interannual variations are important processes in this key region [Rao and Yamagata, 2004;Shinoda and Han, 2005] as well as in the western tropical Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…The southern tropical Indian Ocean (STIO) features remarkable intraseasonal sea surface temperature (SST) variability as a result of ocean-atmosphere interaction between SST and strong atmospheric intraseasonal oscillations (ISOs) [1][2][3][4]. The eastward propagating Madden-Julian Oscillation (MJO), one of the most well-known ISOs, can affect the Indian Monsoon [5] and global climate [6,7] significantly.…”
Section: Introductionmentioning
confidence: 99%